Biosorption of Lead Using the Bacterial Strain, Bacillus subtilis (MTCC 2423) - Gupta, Shivani; Surendran, A.; JosephThatheyus, A. (Journal of Biotechnology and Biomedical Science, 2020)
Lead removal efficiency of the bacterial strain, Bacillus subtilis (MTCC 2423) was tested with 200, 400, 600, 800 and 1000 ppm of lead in minimal broth for a period of ten days. Samples were tested for the level of lead every two days in each concentration and maximum removal was observed after six days of treatment. With the increase in lead concentration, both biomass and lead removal efficiency showed an increase. When tested with immobilized, dead and live cells, maximum removal was observed for immobilized cells. Among the sugars tested, monosaccharide sugars enhanced the biomass of B. subtilis during lead treatment and the results are discussed.
Keywords: Bacteria; Heavy metals; Bioremediation; Industrial effluents; Bacillus subtilis; Isotherm.